Analisis Multi-Peran Kepala Sekolah dalam Meningkatkan Kompetensi Pedagogik Guru - Firmansyah Firmansyah; Kiki Aulia Rahma (P3I Luwu Raya, 2022)
This study discusses the multi-role analysis of the principal in improving the pedagogical competence of teachers in the Palopo Three State Vocational High School, with the aim of this study to determine the multi-role of the Principall in improving the Pedagogic Competence of teachers in the Three Palopo State Vocational High Schools and untuk know the pedagogical competence of teachers at the State Vocational High School of the three Palopo. The method used is a descriptive method with a qualitative approach. The data collection techniques used are observation techniques, interviews, and documentation studies. The subjects of this study consisted of the Principal, and the Teachers' Council. The results of this study show that 1). The role of the school principal in increasing the pedagogical competence of teachers at SMK Negeri 3 Palopo is very good as a leader, manager, educator, supervisor and administrator. The most dominant role of the principal in improving pedagogical teachers at SMK Negeri 3 Palopo is the role of the principal as a motivator. 2). The competence of pedagogic teachers at SMK Negeri 3 Palopo can be described through several aspects, namely the introduction of student characteristics, the application of learning principles, providing support to students, as well as ways, attitudes and strategies of school principals in increasing teacher competence in developing pedagogical teachers.